2016
DOI: 10.7860/jcdr/2016/16455.7295
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Consideration and Potential Complications of Coronary Sinus Catheterisation

Abstract: IntrOductIOnCoronary sinus (CS) and great cardiac vein (GCV) are increasingly being used as a conduit for venous catheterisation for performing various cardiac interventions. These include measurement of energy substrate (glucose and fatty acids) concentrations in CS blood [1] and CS temperature, during retrograde cardioplegia [2]. The coronary venous system is also used for left ventricular or biventricular pacing in patients with severe heart failure The procedure might however become complicated due to obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…Present study traced the origin of diagonal artery and found it to originate either parallel to AIA without crossing between two. 14 The relation between GCV and both arterial branches (AIA and CA) in present study were; no crossing any arterial branches in 6.7% (absence of triangle), GCV superficial to both arteries in eight (33.3%), GCV deep to both arteries in four (16.7%), superficial to one of the artery and deep to another in 12 (50%), parallel to AIA and crossed CA in four (14.3%), parallel to CA and crossed AIA in one (3.6%). GCV was most commonly deep to AIA but in only one case it directly from LCA or from AIA or CA.…”
Section: Resultsmentioning
confidence: 99%
“…Present study traced the origin of diagonal artery and found it to originate either parallel to AIA without crossing between two. 14 The relation between GCV and both arterial branches (AIA and CA) in present study were; no crossing any arterial branches in 6.7% (absence of triangle), GCV superficial to both arteries in eight (33.3%), GCV deep to both arteries in four (16.7%), superficial to one of the artery and deep to another in 12 (50%), parallel to AIA and crossed CA in four (14.3%), parallel to CA and crossed AIA in one (3.6%). GCV was most commonly deep to AIA but in only one case it directly from LCA or from AIA or CA.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of cardiac vascularization have focused largely on the arterial system as coronary artery pathology is responsible for the majority of cardiovascular related mortality and morbidity in humans, especially in developed countries [3][4][5][6]. However, with the advent of new treatment options for various cardiovascular diseases, such as biventricular pacing, ablation procedures, and implantation of medical devices (as with percutaneous mitral annuloplasty), the coronary sinus (CS) is increasingly used to access the coronary venous system [5,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The coverage percentage was calculated according to the formula of Mehra: maximum transverse dimension of the TV/transverse diameter of the CSO × 100. 5 A potentially obstructive TV, which may interfere with the cannulation of the CS, was defined as a non-fenestrated valve covering >75% of the CSO area. Based on our own data, we developed a new TV classification according to its morphology.…”
Section: Methodsmentioning
confidence: 99%
“…If a VV was detected, the diameter of each leaflet was measured, and the coverage percentage of the CS was calculated according to the above-mentioned Mehra formula. 5 Like a potentially obstructive TV, a potentially occlusive VV was defined as a valve covering at least 75% of the CS lumen. The ostium of the vein of Marshall (VOM) was also identified, and its relation to the VV was evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation